Students’ perception toward the plan of tefl module designinfg for college students based on the teacher training - Nirwana Darwis (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This research was done to find out Students’ Perception toward the Plan of TEFL Module Designing Based on Teacher Training. The result of this research will be put into background of the next research in developing TEFL module based on the teacher training approach. A research method applied in this research was survey research. It was held at Islamic State of Institute (IAIN) Bone, Indonesia, in academic year 2017/2018. The samples of this research were 50 English study program students who have been taught TEFL material. The research data were collected through questionnaire and interview. All the samples of this research were involved to respond the questionnaire, and there were only 10 students who involved in follow-up the interview. The results of this research revealed that the mean score of students’ perception was 45.18. Based on the mean scores and interview data, it showed that the students had very high perception toward the Plan of TEFL module designing based on the teacher training.